2011
DOI: 10.1007/s12070-011-0326-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of Naso-Oro-Pharyngeal Structures with the Sleep Architecture in Suspected Obstructive Sleep Apnea

Abstract: The study was conducted to find out the association of various naso-oro-pharyngeal structures with sleep macro-architecture in suspected obstructive sleep apnea subjects. Study included 51 subjects with suspected obstructive sleep apnea. Subjects with possible central apnea and those consuming any substance that can affect sleep architecture were excluded. Level I polysomnography was performed after thorough physical examination. Overnight study was scored in 30 s epochs to find out the polysomnographic variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In the CPAP group, sleep duration and sleep quality as well as indices of sleep-related breathing disorder improved after this intervention; these changes were maintained for 6 months. Although these observations were expected [17][18][19][20] , not all studies have found that CPAP improves sleep quality 21 , and similar results from previous investigations were of shorter duration. Improvement in sleep architecture was correlated with CPAP adherence further strengthening a causal relationship.…”
Section: Discussionmentioning
confidence: 47%
“…In the CPAP group, sleep duration and sleep quality as well as indices of sleep-related breathing disorder improved after this intervention; these changes were maintained for 6 months. Although these observations were expected [17][18][19][20] , not all studies have found that CPAP improves sleep quality 21 , and similar results from previous investigations were of shorter duration. Improvement in sleep architecture was correlated with CPAP adherence further strengthening a causal relationship.…”
Section: Discussionmentioning
confidence: 47%
“…Obviously there are high risks of increased upper airway collapsibility by existence of large tonsils [30][31][32] and macroglossia. 33,34 Mechanical Displacement of the Tongue Clinically, the tongue is frequently manipulated during surgical procedures in the mouth, with compression by instruments (tongue retractor) to avoid accidental injury by surgical instruments or to maintain the surgical view. In contrast to the beneficial effect of tongue protrusion on upper airway collapsibility 35 during sleep, downward displacement (retrograde) of the tongue in supine position might increase upper airway collapsibility during sleep.…”
Section: Bite (Mouth) Openingmentioning
confidence: 99%
“…The systemic character of oral health is highlighted by the interactions between OSA and many oral health issues, such as bruxism, xerostomia, periodontal disease, temporomandibular joint disorders, palatal and dental structural changes, and changes in taste perception [7][8][9][10][11][12][13][14]. Particularly noteworthy are the effects of palatal and dental abnormalities on the severity of OSA [15,16]. The nasal cavity may become narrowed by a high-arched, small palate, which can increase the risk of airway resistance and collapse.…”
Section: Introductionmentioning
confidence: 99%